Language Preferences in Note-Taking for Consecutive Interpreting: Insights from Indonesian EFL Students - Budiarti, Dian (PANYONARA: Journal of English Education, 2025)
In the dynamic field of consecutive interpreting, language choice in note-taking is a critical skill that bridges cognitive processing and ensures the accurate delivery of messages. The present small-scale study investigates the language choice in note-taking for consecutive interpreting practices among Indonesian EFL (English as a Foreign Language) students. This aims to determine whether the students prefer to take notes in English or Indonesian when interpreting between these two languages and to reveal the reasons behind their preferences. This study employed a case study design, analyzing 45 note-taking samples, followed by conducting face-to-face interviews with 4 students to gain a deeper understanding. The findings reveal a significant preference for taking notes in English, irrespective of the direction of interpreting. This preference highlights the students’ inclination towards using English as a medium for cognitive processing and information retention in consecutive interpreting tasks. The results suggest that English proficiency plays a crucial role in the note-taking strategies adopted by Indonesian EFL students. These insights can inform teaching methodologies and curriculum design in interpreter training programs, emphasizing the importance of English proficiency in enhancing interpreting skills.